Um estudo sobre o impacto de tecnologias emergentes: o caso das etiquetas de rádio freqüência na gestão da cadeia de suprimentos - Giordano, Carlos Vital (2007)
The present research aims to study the benefits that could be possible by using the technology supported by radio frequency for identification purposes. The RFID (radio frequency identification) allows the manufacturing the identification tags (smart labels) whose, accordingly fixed in products, boxes, and even in pallets, induct starting sensible modifications in organizations management supply chain, since supported by integrated information systems, both internal and external. The method used was the case study, supported by the creation of some question matrixes used for semi-structured interviews and questions applied on professionals working on development and implementation of fundamental solutions in this core technology, on the environment of relationships involving supply among companies. Initially were identified the contributions brought by companies where interviewed subjects works, for solution of the context studied. Following, the systemic and optimized operational stages were determined for the implementation of those considered more satisfactory ones, considering the quantitative analysis results. The conclusion demonstrates the existence of strong evidences concerning investment returns and operational success, as well as strong evidences on improvement of strategic level, further good evidences of improvements on management level. The results emphasized that, besides the slow evolution at moment, the recommended insertion of technology is mandatory and irreversible, when dissemination will occur. Further, strong similarity was encountered related to development and dissemination of bar code technology, on the supply chain context